The Morphology of Adat: The Celebration of Islamic Holy Day in North Coast Java - AG., Muhaimin (Studia Islamika, 1999)
The main concern of this paper is to throw light on the issue as follow: what days are currently considered as Holy days, for what reason and how is the commemoration or celebration of that day performed. With special reference to Cirebon, a region in North-coast Java about 250 km East of Jakana, This article will discuss this issue at some length. The socio-religious function of these celebrations is also explored.DOI: 10.15408/sdi.v6i3.724